Differences in composition of nutrients in unripe and ripe carica papaya - Rahman, Mohammad Tariqur; Ishak, Ishahir; Suhaimi, Shazlan N. (Karger, 2009)
A study on composition of nutrients in unripe and ripe carica papaya in various countries of the world.